Tauroursodeoxycholic acid prevents hearing loss and hair cell death in Cdh23erl/erl mice. (1st March 2016) - Hu, J.; Xu, M.; Yuan, J.; Li, B.; Entenman, S.; Yu, H.; Zheng, Q.Y.
Highlights: Cdh23 erl/erl mutant mouse is an established model of genetic hearing loss. Tauroursodeoxycholic acid (TUDCA) has been used in diseases related to apoptosis. We studied otoprotective effects and mechanisms of TUDCA in Cdh23 erl/erl mice. TUDCA protects against hearing loss and hair cell death in Cdh23 erl/erl mice. TUDCA partly inhibits the intrinsic apoptosis in Cdh23 erl/erl mouse cochleae. Abstract: Sensorineural hearing loss has long been the subject of experimental and clinical research for many years. The recently identified novel mutation of the Cadherin23 ( Cdh23 ) gene, Cdh23 erl/erl, was proven to be a mouse model of human autosomal recessive nonsyndromic deafness (DFNB12). Tauroursodeoxycholic acid (TUDCA), a taurine-conjugated bile acid, has been used in experimental research and clinical applications related to liver disease, diabetes, neurodegenerative diseases, and other diseases associated with apoptosis. Because hair cell apoptosis was implied to be the cellular mechanism leading to hearing loss in Cdh23 erl/erl mice ( erl mice), this study investigated TUDCA's otoprotective effects in erl mice: preventing hearing impairment and protecting against hair cell death. Our results showed that systemic treatment with TUDCA significantly alleviated hearing loss and suppressed hair cell death in erl mice. Additionally, TUDCA inhibited apoptotic genes and caspase-3 activation in erl mouse cochleae. The data suggest that TUDCA could be a potential therapeutic agent for human DFNB12.